Evaluations of the effects of soil properties and electrical conductivity on the water content reflectometer calibration for landfill cover soils - Kyoungchul KIM; Jaeuk SIM; Tae-Hyung KIM (Soil and Water Research, 2017)
This study presents soil-moisture calibrations using low-frequency (15-40 MHz) time domain reflectometry (TDR) probe, referred to as water content reflectometer (WCR), for measuring the volumetric water content of landfill cover soils, developing calibrations for 28 different soils, and evaluating how WCR calibrations are affected by soil properties and electrical conductivity. A 150-mm-diameter PVC cell was used for the initial WCR calibration. Linear and polynomial calibrations were developed for each soil. Although the correlation coefficients (R2) for the polynomial calibration are slightly higher, the linear calibrations are accurate and pragmatic to use. The effects of soil electrical conductivity and index properties were investigated using the slopes of linear WCR calibrations. Soils with higher electrical conductivity had lower calibration slopes due to greater attenuation of the signal during transmission in the soil. Soils with higher electrical conductivity tended to have higher clay content, organic matter, liquid limit, and plasticity index. The effects of temperature and dry unit weight on WCR calibrations were assessed in clayey and silty soils. The sensor period was found to increase with the temperature and density increase, with greater sensitivity in fine-textured plastic soils. For typical variations in temperature, errors in volumetric water content on the order of 0.04 can be expected for wet soils and 0.01 for drier soils if temperature corrections are not applied. Errors on the order of 0.03 (clays) and 0.01 (silts) can be expected for typical variations in dry unit weight (± 2 kN/m3).